Implikasi Yuridis Pemberlakuan Wacana Earth to Earth Transportation oleh SpaceX - Tasya Ester Loijens (CV Rewang Rencang, 2020)
Rapid technological development allows humans to utilize natural resources that were previously difficult to reach even those in space. With these advances, the law also contributes through international law governing aspects related to the use of space often known as the Five Nations Treaties on Outer Space. In 2017, the CEO of SpaceX (a private American aerospace company), Elon Musk, announced plans to use transportation previously used to move objects from Planet Earth to Space, namely Rockets, for use as public transportation used as a means of mobilization from one place to another on Earth. This is interesting because the concept uses Space after the air surface of Planet Earth, giving rise to new contemplation related to licensing and legality aspects. In this paper, the author intends to examine from the perspective of international law with international arrangements related to air and space law.